Direct Immunosensor Design Based on the Electrochemical Reduction of 4-((4-Nitrophenyl)ethynyl)benzenethiol Monolayers. (22nd August 2011) - Williams, Dwight A.; Williams, Wraegen A. M.; Rhoten, Melissa C.; Crawley, Charlene D.; Ruder, Suzanne
Abstract : The synthesis and characterization of novel N-arylhydroxylamine-based molecular wires are described for use in the site-directed covalent immobilization of whole IgG antibodies onto gold electrode surfaces. The hydroxylamine, electrochemically generated in situ from reduction of the corresponding nitrobenzene, is stable under a wide range of solution conditions and reacts selectively with carbohydrate away from the antibody-binding site to allow the development of immunosensors with maximal activity. Cyclic voltammetric responses have shown a direct correlation between the structure and length of the molecular wire and its stability and concentration at the electrode surface.